INNOVATION OF TRAINING METHOD TO MEET THE NEEDS OF UNIVERSAL STUDENTS IN VIETNAM (2005 - 2020) - Dr. Pham Ngoc Tram (Galaxy International Interdisciplinary Research Journal, 2021)
On the basis of studying the current situation of universitytraining methods, the article focuses on analyzing the innovation of university training methods to meet the needs of students in the context of approaching the Fourth Industrial Revolution with many opportunities and challenges.The article defines new university training to meet the needs of students as an effective way to take care ofpeople’s spiritual and material life, making an important contribution to building a learning society.